2019
DOI: 10.2134/jeq2018.07.0261
|View full text |Cite
|
Sign up to set email alerts
|

Buffer Strips on the Low‐Lying Plain of Veneto Region (Italy): Environmental Benefits and Efficient Use of Wood as an Energy Resource

Abstract: Vegetated buffer strips (VBS) are recognized as a cost-effective way to reduce agricultural nonpoint-source pollution. In agroecosystems with high field fragmentation, only narrow VBS that partially compromise farmers' revenue are accepted. This study aimed to identify some ecosystem services as provided by VBS in terms of soil and water quality, and VBS performance in terms of wood for energy purposes. Buffer strip design (3 vs. 6 m wide) and composition were considered to define best practices for wood use a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 42 publications
2
8
1
Order By: Relevance
“…However, the meta‐analysis found that buffering effectiveness was reduced with buffer zone age and was unrelated to width. In contrast, other studies in the current compilation support NO 3 reduction effectiveness increasing with width (Dal Ferro et al, 2019; Jaynes and Isenhart, 2019). The latter studies examined narrower buffers and possibly identified minimum sizes (e.g., below ∼5 m where N interception became negligible compared with input loads).…”
Section: New Contribution Of Knowledge To the Topiccontrasting
confidence: 95%
See 4 more Smart Citations
“…However, the meta‐analysis found that buffering effectiveness was reduced with buffer zone age and was unrelated to width. In contrast, other studies in the current compilation support NO 3 reduction effectiveness increasing with width (Dal Ferro et al, 2019; Jaynes and Isenhart, 2019). The latter studies examined narrower buffers and possibly identified minimum sizes (e.g., below ∼5 m where N interception became negligible compared with input loads).…”
Section: New Contribution Of Knowledge To the Topiccontrasting
confidence: 95%
“…Dal Ferro et al (2019) found that 6‐m buffer strips achieved reductions in total suspended solids (64%), total P (31%), and herbicides (45–98%), whereas 3‐m buffers were less effective and even enhanced some pollutant losses to watercourses relative to controls. Subsidies for these buffers were for management of buffers for trees.…”
Section: New Contribution Of Knowledge To the Topicmentioning
confidence: 99%
See 3 more Smart Citations